Using SSR-HRM to Identify Closely Related Species in Herbal Medicine Products: A Case Study on Licorice - Jingjian Li; Chao Xiong; Xia He; Zhaocen Lu; Xin Zhang; Xiaoyang Chen; Wei Sun (Frontiers Media S.A., 2018)
Traditional herbal medicines have played important roles in the ways of life of people around the world since ancient times. Despite the advanced medical technology of the modern world, herbal medicines are still used as popular alternatives to synthetic drugs. Due to the increasing demand for herbal medicines, plant species identification has become an important tool to prevent substitution and adulteration. Here we propose a method for biological assessment of the quality of prescribed species in the Chinese Pharmacopoeia by use of high resolution melting (HRM) analysis of microsatellite loci. We tested this method on licorice, a traditional herbal medicine with a long history. Results showed that nine simple sequence repeat (SSR) markers produced distinct melting curve profiles for the five licorice species investigated using HRM analysis. These results were validated by capillary electrophoresis. We applied this protocol to commercially available licorice products, thus enabling the consistent identification of 11 labels with non-declared Glycyrrhiza species. This novel strategy may thus facilitate DNA barcoding as a method of identification of closely related species in herbal medicine products. Based on this study, a brief operating procedure for using the SSR-HRM protocol for herbal authentication is provided.